Acceptability and Nutritiont Contents of Soft Cookies Substitued with Mocaf Flour with the Addition of Moringa Leaves as an Alternative Snack for Teenage Girl with Anemia - Kristian, Sarah Aurelia; Rita Ismawati (Jurnal Gizi dan Kesehatan Nusantara, 2024)
Anemia is a health issue that requires special attention. According to the 2018 Basic Health Research (Riskesdas) data, the incidence of anemia among teenager aged 15-24 years is 32.0%, with a higher prevalence in females compared to males. Teenage girls (ages 12-19) need additional nutritional intake to help increase hemoglobin production and prevent anemia. An approach is the development of functional products high in iron, such as soft cookies made with mocaf flour and moringa leaves. This research is a Pure Experimental study designed as a Completely Randomized Design. Sensory test data was collected from 30 panelists across six formulations developed: M1K1 (50% mocaf flour + 10 g moringa leaves), M1K2 (50% mocaf flour + 20 g moringa leaves), M1K3 (50% mocaf flour + 30 g moringa leaves), M2K1 (75% mocaf flour + 10 g moringa leaves), M2K2 (75% mocaf flour + 20 g moringa leaves), and M2K3 (75% mocaf flour + 30 g moringa leaves). The data was analyzed using the Kruskal-Wallis test and Mann-Whitney test as follow-up tests. The results from the six formulations indicate that there is an effect of substituting mocaf flour with the addition of moringa leaves on the acceptance of aroma and taste (p<0.05); however, there was no effect on the acceptance of color and texture (p>0.05), with the best product being M1K1. The nutritional content analysis of the soft cookies with the best substitution of mocaf flour and moringa leaves, or formula M1K1, based on laboratory testing the results showed that the intake contributes to the Recommended Dietary Allowance (RDA) for teenage girl by providing 5.52 mg (36.8%) of iron and 3.21 mg (4.3-4.8%) of vitamin C.